THE INFLUENCE OF HEALTH PROMOTION ON THE LEVEL OF KNOWLEDGE AND ATTITUDE REGARDING CLEAN AND HEALTHY LIVING BEHAVIOR - Siti Nur Farida; Ardiyanti Hidayah; Rista Dian Anggraini (Literasi Kesehatan Husada)
Background: The elementary school age period is often referred to as the intellectual period. At the developmental stage, elementary school children are 6-12 years old. During this period, children are relatively easier to educate than before and after. During this period, children are more likely to experience various kinds of diseases. Health problems that often occur in children are caused by a lack of clean and healthy living behavior. Health promotion is an effort in health education in schools.